Prescription audit in outpatient department of a teaching hospital of North East India - Saha, Arjun; Bhattacharjya, Himadri; Sengupta, Bitan; Debbarma, Rajkishore (International Journal of Research in Medical Sciences, 2018)
Background: Quality of the prescriptions generated from OPD of Agartala Government Medical College and Govinda Ballabh Pant Hospital is never assessed. The study objectives were to find out the quality in terms of legibility, completeness and adherence to WHO core prescribing indicators of the prescriptions generated from OPD of this hospital. Methods: This hospital based cross-sectional study was conducted during 11th to 16th December 2017 among 442 prescriptions picked up from 12 OPDs by multi stage sampling technique and examined using a checklist designed to assess adherence to WHO core prescribing indicators, legibility and completeness. Data entry and analysis were performed with computer using SPSS 15.0. Descriptive statistics and Chi-square test were used to present data. Results: Total 1169 items were prescribed in 442 prescriptions. Only 50.90% prescriptions were legible. Average number of drugs prescribed per encounter was 2.64, 223 (19.07%) were generic drugs, 14 (1.19%) were injections, 176 (15.05%) were antibiotics and 618 (52.86%) items were from the national essential drug list. History was written in 62.70%, findings were written in 52.70%, diagnosis was written in 40.00%, 87.80% prescriptions contained no review instructions, 84.60% contained complete directions to the pharmacist, 87.10% did not contain complete direction to the patients and signature section was incomplete in 99.80% of the prescriptions. Significantly higher proportions of the high ranked prescribers wrote generic items, review instructions and complete directions to the patients in their prescriptions (p < 0.05). Conclusions: Most of the prescriptions generated from OPD of Agartala Government Medical College and Govinda Ballabh Pant Hospital were found to be incomplete, about half of them were illegible and sizeable proportions did not adhere to the WHO core prescribing indicators.